A baculoviral system for the production of human β‐glucocerebrosidase enables atomic resolution analysis. Issue 6 (4th June 2020) - Rowland, Rhianna J.; Wu, Liang; Liu, Feng; Davies, Gideon J.
Abstract : Active human β‐glucocerebrosidase was produced in baculovirus‐transduced insect cells, purified and crystallized to yield a 0.98 Å resolution unliganded structure and a trapped covalent intermediate structure with 2‐deoxy‐2‐fluoro‐β‐d ‐glucopyranoside. Abstract : The lysosomal glycoside hydrolase β‐glucocerebrosidase (GBA; sometimes called GBA1 or GCase ) catalyses the hydrolysis of glycosphingolipids. Inherited deficiencies in GBA cause the lysosomal storage disorder Gaucher disease (GD). Consequently, GBA is of considerable medical interest, with continuous advances in the development of inhibitors, chaperones and activity‐based probes. The development of new GBA inhibitors requires a source of active protein; however, the majority of structural and mechanistic studies of GBA today rely on clinical enzyme‐replacement therapy (ERT) formulations, which are incredibly costly and are often difficult to obtain in adequate supply. Here, the production of active crystallizable GBA in insect cells using a baculovirus expression system is reported, providing a nonclinical source of recombinant GBA with comparable activity and biophysical properties to ERT preparations. Furthermore, a novel crystal form of GBA is described which diffracts to give a 0.98 Å resolution unliganded structure. A structure in complex with the inactivator 2, 4‐dinitrophenyl‐2‐deoxy‐2‐fluoro‐β‐d ‐glucopyranoside was also obtained, demonstrating the ability of this GBA formulation to be used in ligand‐binding studies. In light of its purity, stability and activity, the GBA production protocol described here should circumvent the need for ERT formulations for structural and biochemical studies and serve to support GD research.